NPM1/B23: A Multifunctional Chaperone in Ribosome Biogenesis and Chromatin Remodeling - Mikael S. Lindström (Biochemistry Research International)
At a first glance, ribosome biogenesis and chromatin remodeling are quite different processes, but they share a common problem involving interactions between charged nucleic acids and small basic proteins that may result in unwanted intracellular aggregations. The multifunctional nuclear acidic chaperone NPM1 (B23/nucleophosmin) is active in several stages of ribosome biogenesis, chromatin remodeling, and mitosis as well as in DNA repair, replication and transcription. In addition, NPM1 plays an important role in the Myc-ARF-p53 pathway as well as in SUMO regulation. However, the relative importance of NPM1 in these processes remains unclear. Provided herein is an update on the expanding list of the diverse activities and interacting partners of NPM1. Mechanisms of NPM1 nuclear export functions of NPM1 in the nucleolus and at the mitotic spindle are discussed in relation to tumor development. It is argued that the suggested function of NPM1 as a histone chaperone could explain several, but not all, of the effects observed in cells following changes in NPM1 expression. A future challenge is to understand how NPM1 is activated, recruited, and controlled to carry out its functions.